The “blue community” of the Indian Ocean: cooperation, challenges and prospects for marine environmental protection among South Asian countries - Zhang, Hanrui; Wan, Jia (Frontiers in Marine Science, 2025)
The five South Asian countries surrounding the northern edge of the Indian Ocean — India, Pakistan, Bangladesh, Sri Lanka and the Maldives — boast diverse marine ecosystems ranging from mangrove deltas to coral atolls. The establishment of binding legal obligations for marine environmental protection has made safeguarding marine ecosystems one of the core issues in the global governance system. Taking a legal and institutional approach, this article analyses the main content and characteristics of the marine environmental protection systems of five South Asian countries. Through text analysis, comparative legal research and case evaluation, it aims to answer three key questions:(1) The degree to which current domestic laws in South Asian coastal countries align with international marine environmental norms.(2) The existing regional cooperation mechanisms and interaction models for marine environmental protection in South Asian coastal countries, based on principles of international law and global best practices. (3) There are structural and enforcement bottlenecks in the legal mechanisms for marine environmental protection and cooperation among South Asian countries. The findings indicate that despite certain advancements, significant challenges remain in building a “blue community” in the Indian Ocean region.